PENINGKATAN PENALARAN MATEMATIKA MELALUI STRATEGI NUMBERED HEADS TOGETHER BERBASIS DISCOVERY LEARNING (PTK pada Siswa Kelas X Akuntansi 1 Semester Genap SMK N 1 BanyudonoTahun 2016/2017) - Latif Purnama Sari, Nikmah (2017)
The purpose of this study is to improve mathematical reasoning through Numbered Heads Together strategies based on Discovery Learning in grade X Accounting 1 of SMK N 1 Banyudono. This type of research is a classroom action research. The subjects were mathematics teacher class X Accounting 1 as a subject that gives action and 36 of students consisting of 34 females students and 2 males students as subjects receiving action. Implementation of a class action was conducted in two cycles consisting of three meetings. The technique of analyzing data is using observation, testing methods, field notes and documentation. Data were analyzed using data collection, data reduction, data display and conclusion. To check the validity of the data the researchers did investigator triangulation.The result showed an Increase in mathematical reasoning with an indicator: 1) the ability of the students filed allegations before action (there is no supporting data), in the first cycle of 27.78% and 73.52% in the second cycle. 2) students ability do manipulation mathematics before the act 27.78%, in cycle I 52.94% and in cycle II 97.14%. 3) the ability of students to draw conclusions before the act of 30.56%, 29.56% in the first cycle and the second cycle 97.14%.